The Role of Speech Therapy in Sialorrhea Management and Quality of Life: A Retrospective Study - Sofia Eva Olsson; Stephen Reed Chorney; Allison Tidwell Brown; Romaine Fitzgerald Johnson; Yann‐Fuu Kou (Laryngoscope Investigative Otolaryngology)
ABSTRACT Objective The objective of this study is to determine the impact of an intensive and a less intensive speech therapy regimen on pediatric sialorrhea patient and caregiver quality of life (QoL) as described by drooling impact scales (DIS). Methods A retrospective chart review included all pediatric patients from a secretion management clinic. There were two outpatient speech therapy programs: intensive (4 sessions/week for 3 weeks) and less intensive (2 sessions/week for 3 months). Both regimens included similar interventions including neuromuscular electrical stimulation and facial taping. The primary outcome measure was reduction in caregiver reported DIS after completing their designated program. Children observed without therapy also obtained DIS assessments overtime to measure potential changes in QoL. Results There were 49 patients included in the study with a mean age of 7.5 years (SD = 4.6). The most common comorbidities were global developmental delay (n = 47; 96%), epilepsy (n = 35; 71%), and cerebral palsy (n = 32; 65%). After initial evaluation, 30 patients underwent speech therapy with significantly improved DIS scores compared to the 19 who had no therapy (43.4 vs. 54.5, p = 0.03). Of these 30, 16 (33%) underwent intensive therapy with mean DIS improving from 63.5 to 47.2 (p = 0.006). Fourteen (29%) completed the less intensive regimen with mean DIS improving from 51.9 to 39.1 (p = 0.07). There were 19 (39%) patients who underwent no therapy and mean DIS remained unchanged from 55.6 to 54.5 (p = 0.86). Conclusion Sialorrhea can drastically impact patients and their families. An intensive speech therapy program is associated with improved QoL as described by the DIS. Speech therapy should be considered as an effective treatment modality to improve outcomes for pediatric sialorrhea. Level of Evidence 2.